Knowledge management, customer satisfaction and organizational image discriminating certified from non-certified (ISO 9001) municipalities - Brito, Elisabeth (2021)
Purpose The purpose of this paper is to ascertain the extent to which knowledge management (KM), customer satisfaction (CS) and organizational image (OI) discriminate quality-certified municipalities from non-certified ones (ISO 9001). Design/methodology/approach An empirical study was carried out involving 81 Portuguese municipalities (40 certified, 41 non-certified), paired in a random sampling procedure. The Knowledge Management Questionnaire (n=1,372 municipality employees), the Customer Satisfaction Questionnaire and the Organizational Image Questionnaire (n=3,096 residents) were applied. Multiple discriminant analysis was performed. Findings The results indicate that certified and non-certified municipalities are distinct based on a function that considers KM (competitive orientation and formal KM practices), CS (intangible and tangible factors) and OI (favorable image). Research limitations/implications The findings need further validation in other countries. However, the results highlight the importance of quality certification for both employees and residents. Practical implications The results encourage local public administration organizations to introduce and maintain quality certification. Originality/value This research is the only one, to the authors’ knowledge, that simultaneously explores organizational processes of KM, CS and OI in local public administration. The sampling procedure and the information from diverse data sources are unique contributions. The conclusions may aid practitioners and scholars in understanding these organizational phenomena in the context of quality-certified and quality non-certified municipalities.